The Influence Of Financial Distress, Opinion Shopping, Debt Default, And Audit Tenure On The Acceptance Of A Going Concern Audit Opinion - Musyaffa, Muhammad Shidqi; Putri, Intan Lifinda Ayuning (Telaah Ilmiah Akuntansi dan Perpajakan, 2024)
This study aims to analyze the influence of financial distress, opinion shopping, debt default, and audit tenure on the acceptance of the going concern audit opinion in non-financial service sector companies listed on the Indonesia Stock Exchange (IDX) for 2020-2022. The data used is secondary data obtained from annual financial reports and independent auditor reports. This research employs logistic regression to examine the relationship between the independent and dependent variables. The results show that debt default positively and significantly impacts the acceptance of the going concern audit opinion. However, financial distress, opinion shopping, and audit tenure do not significantly affect the acceptance of the going concern audit opinion. These findings highlight the importance of debt default in auditors' company continuity assessments. At the same time, other factors such as financial distress and audit tenure may not significantly influence the outcome. This study provides insights for auditors and companies in understanding the factors affecting the acceptance of the going concern audit opinion, especially in the post-pandemic context. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh financial distress, opinion shopping, debt default, dan audit tenure terhadap penerimaan opini audit going concern pada perusahaan sektor jasa non-keuangan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2020-2022. Data yang digunakan merupakan data sekunder yang diperoleh dari laporan keuangan tahunan dan laporan auditor independen. Penelitian ini menggunakan metode regresi logistik untuk menguji hubungan antara variabel-variabel independen dan dependen. Hasil penelitian menunjukkan bahwa debt default berpengaruh positif dan signifikan terhadap penerimaan opini audit going concern. Namun, variabel financial distress, opinion shopping, dan audit tenure tidak menunjukkan pengaruh signifikan terhadap penerimaan opini audit going concern. Temuan ini menegaskan pentingnya debt default dalam penilaian auditor terhadap keberlangsungan hidup perusahaan, sedangkan faktor-faktor lain seperti financial distress dan audit tenure tidak memberikan dampak yang signifikan. Penelitian ini memberikan wawasan bagi para auditor dan perusahaan dalam memahami faktor-faktor yang mempengaruhi penerimaan opini audit going concern, khususnya dalam kondisi pasca-pandemi.